MAP OF EDIBLE ARACEAE BASED ON ABIOTIC FACTORS IN GOWA REGENCY, SOUTH SULAWESI - Hafsah Hafsah; Rodiyati Azrianingsih; Mashuri Masri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2018)
This study aims to create a distribution map and find out the relationship between the distribution of edible Araceae and abiotic factors in Gowa Regency, South Sulawesi. Edible Araceae explorations were carried out in 18 sub-districts in November 2016 to September 2018. Edible Araceae which was found to be marked with GPS location, documented with a camera, and measured abiotic factors including altitude, air temperature, soil temperature, light intensity, soil pH, humidity soil, air humidity and soil organic matter. The types of Araceae found included 9 species from 4 genera, namely Xanthosoma sagittifolium (L.) Schott., Xanthosoma nigrum, Colocasia esculenta (L.) Schott., Colocasia esculenta, Alocasia calidora, Alocasia macrorrhiza (L.) Schott. Amorphophallus muelleri Blume, Amorphophallus paeoniifolius, Amorphophallus variabilis Blume. Distribution of edible Araceae in Gowa Regency, South Sulawesi includes coastal areas (<100 m asl), lowlands (100-400 m asl) and highlands (<400 m asl). The distribution of Araceae which is affected by light intensity is Xanthosoma and Alocasia, while the distribution of Colocasia is influenced by altitude, soil organic matter, and soil moisture and Amorphophallus is influenced by soil pH. Araceae conservation strategy compiled based on species data, habitat preference, utilization and distribution of Araceae is expected to be used for the establishment of community business activities for the management of Araceae in each village that has an Araceae distribution.